A Few Words About the Founder of the Macedonian Modern Sculpture - Marković, Kamenko M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This paper discusses the life and work of Dima Todorovski, the founder of the Macedonian modern sculpture. Dimo Todorovski was born in Thessaloniki in 1910. He finished the Art School, the sculpture department, in Belgrade in 1935. He lived and worked in Skopje from 1942 until his death in 1983. During his career, he made an impressive number of sculptures among which are portraits, lovely female nudes, figures of men in motion, and other pieces related to the WWII. His best pieces include: The Portrait of the Artist’s Mother, A Peasant Woman Portrait, The Pit, The Macedonian Pieta, A Girl,  A monument in honour of Koco Racin, The Miladinov Brothers, St. Kliment Ohridski.